Buckling analysis of functionally graded materials structures with enhanced solid-shell elements and transverse shear correction. (15th November 2015) - Hajlaoui, A.; Jarraya, A.; El Bikri, K.; Dammak, F.
Abstract: In this paper, the buckling behavior of functionally graded material (FGM) structures is investigated using the enhanced assumed strain (EAS) solid-shell element based on first-order shear deformation concept. Thus, a computational algorithm, for any type of laminates composites and/or FGM, is proposed for the shear correction factors estimation. Material properties are varied continuously in the thickness direction according to different distributions. This finite element is used to study the buckling behavior of FGM structures and to investigate the influence of same parameters on the buckling load. Comparisons of numerical results among existing ones show the performance of the developed elements.